151k views
3 votes
Which of the following expressions are equivalent? Please explain so I can understand.

Which of the following expressions are equivalent? Please explain so I can understand-example-1

1 Answer

4 votes

Answer:

B and D

Explanation:

Expression B = 1/
x^(-1) = 1/ (1/x) = x

Expression D =
x^(1/3)
x^(1/3)
x^(1/3)

=
x^(1/3 + 1/3 + 1/3)

=
x^(1)

= x

as shown above the both the value of B and D are equal to x and hence the expressions are equivalent

User Akshansha Singhal
by
4.9k points